Removal of cyclohexane and ethanol from air in biotrickling filters inoculated with Candida albicans and Candida subhashii - Piotr Rybarczyk; Milena Marycz; Bartosz Szulczyński; Anna Brillowska-Dąbrowska; Agnieszka Rybarczyk; Jacek Gębicki (Archives of Environmental Protection, 2021)
This paper presents investigations on the removal of cyclohexane and ethanol from air in polyurethane- -packed biotrickling filters, inoculated with Candida albicans and Candida subhashii fungal species. Results on process performance together with flow cytometry analyses of the biofilm formed over packing elements are presented and discussed. The results indicate that the presence of ethanol enhances the removal efficiency of cyclohexane from air. This synergistic effect may be attributed to both co-metabolism of cyclohexane with ethanol as well as increased sorption efficiency of cyclohexane to mineral salt medium in the presence of ethanol. Maximum elimination capacities of 89 g m-3 h-1 and 36.7 g m-3 h-1 were noted for cyclohexane and ethanol, respectively, when a mixture of these compounds was treated in a biofilter inoculated with C. subhashii. Results of flow cytometry analyses after 100 days of biofiltration revealed that about 91% and 88% of cells in biofilm remained actively dividing, respectively for C. albicans and C. subhashii species, indicating their good condition and ability to utilize cyclohexane and ethanol as a carbon source.